Al2O3/glass/hBN composites with high thermal conductivity and low dielectric constant for low temperature cofired ceramic applications. Issue 1 (2nd January 2021) - Bilaç, Oğuzhan; Duran, Cihangir
ABSTRACT: Al2 O3 /glass/hBN composites were successfully fabricated for the LTCC applications. Alignment and homogeneous distribution of the platelet hBN particles during tape casting allowed high hBN (5 wt%) loading as well as facilitated densification at 800°C (density of 2.65 g/cm 3, apparent porosity of 0.7%). XRD results proved that hBN neither chemically reacted with the other phases nor decomposed with temperature, which was critical to increase thermal conductivity and at the same time to decrease dielectric constant. Dielectric constant of the dense composites decreased (or, alternatively, enhanced) with increasing hBN content from 7.3 for the 0 wt% hBN to 6.55 for the 5 wt% hBN at 5 MHz. In addition, hBN addition strongly improved the mean thermal conductivity from 1.86 W/m·K for the 0 wt% hBN to 2.43 W/m·K for the 5 wt% hBN between 75°C and 250°C. Therefore, the hBN phase itself effectively optimized both dielectric and thermal properties at the same time and made the Al2 O3 /glass/hBN composites a promising candidate for the LTCC applications.